Water quality and zooplankton monitoring at the seawater circuit of a mollusk hatchery - Hoffmeyer, Monica Susana (2006)
Seawater quality in mollusc hatcheries has been identified as one topic of high concern because of its implications in larval performance. This aspect, however, has received little or no attention from the scientific point of view. The only literature about this topic is a general compilation about water quality for aquaculture systems (Anonymous 1977). This gap in the available information may be mainly that periodic adjustments performed in hatcheries are routine protocols, the results of which are filed as internal reports and seldom reach the scientific literature. Research done on this subject has dealt primarily with water quality and the composition of effluents from hatcheries and other aquaculture systems and their potential reuse for other purposes, such as agriculture and he culture of secondary aquatic organisms (Van Rijn 1996, Lin et al. 2002) There have also been studies associated with the effects of different treatments of seawater aimed at improving the quality of bivalve larvae (Utting et al. 1983, Chen 1984, Jaeckle and Manahan 1989). Our study was triggered by the occasional finding of different types of plankton, mainly copepod microcrustaens, in the water used for larval culture in a mollusc hatchery. The assessment of water quality and biota throughout the entire water circuit was undertaken to improve the intake system and the treatment methods employed in conjunction with the water that circulates within the hatchery. This study is the first of its kind performed in Argentina. We present here the results of a survey performed during a year in the hatchery during which water quality was monitored with regard to its physical and chemical properties, including temperature, salinity, pigments, organic matter. Planktonic species richness and total abundance, species abundance and the presence of non-planktonic organisms were also assessed